ING4 alleviated lipopolysaccharide‐induced inflammation by regulating the NF‐κB pathway via a direct interaction with SIRT1. Issue 2 (14th January 2020) - Yang, Yunshu; Liu, Yang; He, Xiang; Yang, Fangfang; Han, Shichao; Qin, Anhui; Wu, Gaofeng; Liu, Mengdong; Li, Zhenzhen; Wang, Jing; Yang, Xuekang; Hu, Dahai
Abstract: Sepsis is a complex inflammatory disorder in which high mortality is associated with an excessive inflammatory response. Inhibitor of growth 4 (ING4), which is a cofactor of histone acetyltransferase and histone deacetylase complexes, could negatively regulate this inflammation. However, the exact molecular signaling pathway regulated by ING4 remains uncertain. As a pivotal histone deacetylase, Sirtuin1 (SIRT1), which is widely accepted to be an anti‐inflammatory molecule, has not been found to be linked to ING4. This study investigated how ING4 is involved in the regulation of inflammation by constructing lipopolysaccharide (LPS)‐induced macrophage and mouse sepsis models. Our results revealed that ING4 expression decreased, whereas the levels of proinflammatory cytokines increased in LPS‐stimulated cultured primary macrophages and RAW 264.7 cells. ING4 transfection was confirmed to alleviate the LPS‐induced upregulation of proinflammatory cytokine expression both in vitro and in vivo . In addition, ING4‐overexpressing mice were hyposensitive to an LPS challenge and displayed reduced organ injury. Furthermore, immunoprecipitation indicated a direct interaction between ING4 and the SIRT1 protein. Moreover, ING4 could block nuclear factor‐kappa B (NF‐κB) P65 nuclear translocation and restrict P65 acetylation at lysine 310 induced by LPS treatment. These results are the first to clarify that the anti‐inflammatory role of ING4 is associated with SIRT1, through which ING4 inhibits NF‐κB signaling activation. Our studies provide a novel signaling axis involving ING4/SIRT1/NF‐κB in LPS‐induced sepsis. Abstract : Inhibitor of growth 4 (ING4) could reduce upregulation of proinflammatory cytokines in lipopolysaccharide‐induced inflammation both in vitro and in vivo . ING4 was found to interact with Sirtuin1 (SIRT1), and restrain the nuclear translocation and acetylation of nuclear factor‐kappa B P65 which was related to SIRT1.